Estudo transversal sobre o conhecimento da transmissão viral e as atitudes em relação aos cuidados com as escovas dentárias entre pacientes infectados com o HCV - Garbin, Cléa Adas Saliba [UNESP]; de Souza, Neila Paula [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Villar, Livia Melo (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
Hepatitis C virus (HCV) is transmitted mainly by parenteral route, although, some studies have pointed the potential of transmission by sharing infected instruments, like toothbrushes. The aim of this study was to investigate the knowledge about viral transmission among HCV infected individuals and attitudes regarding toothbrush care. A cross-sectional study was conducted among 112 HCV-infected individuals from Uberlandia City, Minas Gerais State (Southeast Brazil). Data were collected through a questionnaire containing demographic data and other questions (correct responses were given one point, incorrect and uncertain responses were given zero point) about knowledge of HCV transmission (6 items in total; scores lower than 4 points indicated poor knowledge level and scores equal or higher than 4 indicated good knowledge level); attitudes regarding toothbrush care (7 items; scores 0 to 3 indicated inadequate attitudes, and scores higher than 3 indicated adequate attitudes). The statistical analysis included Chi-square test, Exact Fisher’s test and Maximum Likelihood Estimation (p < 0.05 was considered significant). Out of the 112 questionnaires distributed, 85 (response rate: 75.9%) were included. Most individuals were male (60%), Caucasian (69.4%), aged more than 51 years (51.7%), had attended pre-school (35.1%), and had incomes up to $525.2 per month (49.4%). Fifty four percent of individuals showed good Knowledge level of HCV transmission; 43.5% did not identify HCV transmission through toothbrushes and 80% did not believe in HCV transmission by saliva. A significant association were observed between Knowledge level of HCV and age (p= 0.020); and education level (p= 0.000). Forty-five HCV-infected individuals (64.70%) had adequate attitudes regarding toothbrushes care. Significant associations were observed between toothbrush care level and: age (p= 0.005); education level (p= 0.000); and family income (p= 0.038). HCV-infected individuals showed good knowledge level about main aspects of HCV infection and adequate attitudes regarding toothbrush care.
A cross sectional study regarding HCV patients’ knowledge about viral transmission and attitudes regarding toothbrush care
Keywords: Hepatitis C virus; Knowledge; Saliva; Toothbrushing; Transmission